Case Report: Reflection on a case of splenic abscess in a child - Zhou, Tao; Liu, Yongfang (Frontiers in Pediatrics, 2024)
Splenic abscesses (SA), especially in children, are rare in clinical practice. The missed diagnosis rate of SA is high and the probability of rapidly diagnosing it is relatively low due to its low incidence rate and the presence of non-specific clinical symptoms and imaging manifestations. Antibiotics are the primary treatment for SA; however, ultrasound-guided percutaneous puncture suction or drainage, and splenectomy are other effective treatment strategies. In this study, we report one case of SA in a 16-year-old male patient who presented with abdominal pain, fever, and cough, and the therapeutic effect was unsatisfactory (recurrent fever). After admission, the patient was diagnosed with a solitary SA by abdominal CT with contrast and upper abdominal MRI; fever and abdominal pain were relieved and the SA gradually disappeared after antibiotic treatment.